2021
DOI: 10.1016/j.atherosclerosis.2021.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Improving the identification of patients with a genetic diagnosis of familial hypercholesterolaemia in primary care: A strategy to achieve the NHS long term plan

Abstract: Background and aims: We aimed to validate a nurse-led process using electronic health records to identify those at risk of familial hypercholesterolaemia (FH) for genetic diagnosis in primary care. Methods: Those at risk of FH were identified using searches developed and refined locally and implemented in primary care by a trained nurse; they were invited for further assessment and genetic testing if indicated. Family members at risk of FH were identified and invited for cascade testing. Results: In total 94,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Four studies implemented the existing clinical diagnostic criteria into their healthcare system electronic health records (EHRs) as a screening tool to identify previously unrecognized individuals with FH. Similar rates of individuals requiring additional diagnostic screening for FH were found: 1 in 245 (7468/1 831 658) met the Make Early Diagnoses Prevent Early Deaths (MEDPED) criteria [20], 1 in 150 (303/45 123) met the Simon Broome (SB) Criteria [21], and 1 in 183 (269/49 321) [21] and 1 in 119 (351/41 937) [22] met the Dutch Lipid Clinic Network Criteria (DLCN). The screening positive rate for FH was higher, 1 in 5 (84/469), when the DLCN criteria were applied to EHRs of those with known severe hypercholesterolemia [23].…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Four studies implemented the existing clinical diagnostic criteria into their healthcare system electronic health records (EHRs) as a screening tool to identify previously unrecognized individuals with FH. Similar rates of individuals requiring additional diagnostic screening for FH were found: 1 in 245 (7468/1 831 658) met the Make Early Diagnoses Prevent Early Deaths (MEDPED) criteria [20], 1 in 150 (303/45 123) met the Simon Broome (SB) Criteria [21], and 1 in 183 (269/49 321) [21] and 1 in 119 (351/41 937) [22] met the Dutch Lipid Clinic Network Criteria (DLCN). The screening positive rate for FH was higher, 1 in 5 (84/469), when the DLCN criteria were applied to EHRs of those with known severe hypercholesterolemia [23].…”
Section: Resultsmentioning
confidence: 60%
“…The screening positive rate for FH was higher, 1 in 5 (84/469), when the DLCN criteria were applied to EHRs of those with known severe hypercholesterolemia [23]. Diagnostic evaluation for FH in individuals identified by these EHR screening initiatives found 18–36% met clinical criteria [21–23]. However, the percentage of these individuals with a genomic risk variant for FH ranged from 25 to 68% depending on the study [20,21,23] meaning that using genetics as the sole indicator for a diagnosis of FH would miss many individuals who met clinical diagnostic criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Other approaches have also been proposed. In 2021, Birnbaum et al ( 20 ) and Ingoe et al ( 23 ) demonstrated increased diagnosis of FH and utilization of genetic testing after system-wide scanning of the EHR to identify patients at high risk; and Soper et al ( 59 ) described a genomic screening program that identified individuals with variants in TTR , none of whom had a previous diagnosis of hereditary transthyretin amyloidosis. Adopting implementation science frameworks and practices may also facilitate the uptake of guideline-directed genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…Some strategies included specialist nurse (n=2) and specialist lipidologist (n=3) involvement in the review process. Specialist nurses triaged potential FH cases for genetic testing and also independently screened for FH index cases 27,28 .…”
Section: Strategies Employedmentioning
confidence: 99%